Verhulst populational model applied to distributed power control in DS/CDMA - Paul Jean Etienne Jeszensky; Taufik Abrão; Tadeu Junior Gross (Semina: Ciências Exatas e Tecnológicas, 2005)
In this paper the continuous dynamic model of Verhulst is used. It had been initially elaborated to describe the population growth of biological species with food restriction and physical space, in order to synthesize a new distributed power control algorithm (DPCA), applicable in direct sequence code division multiple access (DS-CDMA) systems. The discretization of the corresponding differential equation is accomplished via numeric integration Euler method (NIE). The properties of the proposed recursive algorithm, as Euclidian distance from optimum vector after convergence, convergence speed, normalized mean squared error (NSE), average power consumption per user and implementation complexity, are investigated through simulations. The simulation results are confronted with the other DPCAs: the classic algorithm derived by Foschini and Miljanic and the sigmoidal by Uykan and Koivo. With estimate errors, the proposed DPCA showed smaller discrepancy from the optimum power vector allocation after convergence and better convergence. Additionally, the Gerchgorin Circles theory (GC) is applied for the feasibility of the power allocation problem.